Luther's Small Catechism with Explanation - Martin Luther 1483-1546. (USA Concordia Publishing House, 1991)
Contains the basic principles of the Lutheran religion with some explanation.
Translation of: Kleine Katechismus.
"Based on A short explanation of Dr. Martin Luther's Small catechism, c1943, slightly revised 1965 by Concordia Publishing House"--T.p. verso.
Includes indexes.
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Lutheran Church -- Catechisms -- English; Theology; Catechisms, English; Lutheran Church -- Catechisms; Catechisms